2017
DOI: 10.4172/2155-6148.1000767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Pre-anesthetic Communication on Preoperative Patient Anxiety

Abstract: Background: The preanesthetic visit influences patient satisfaction and medical outcome. Providing relevant information may reduce anxiety. This study aimed to evaluate whether training for a structured interview technique improves communication skills, resulting in increased patient satisfaction and reduced patient's anxiety and fear of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…They have used predefined question prompt lists for the consultation session held 1-3 weeks before the surgical schedule. Another study on a structured communication between patients and anesthesiologists showed reduced anxiety and fear of anesthesia, particularly in younger patients compared to standard interview techniques ( 65 ). Notably, the structured interview had a significantly shorter duration compared to the routine sessions.…”
Section: Interview Conversation and Communication Strategiesmentioning
confidence: 99%
“…They have used predefined question prompt lists for the consultation session held 1-3 weeks before the surgical schedule. Another study on a structured communication between patients and anesthesiologists showed reduced anxiety and fear of anesthesia, particularly in younger patients compared to standard interview techniques ( 65 ). Notably, the structured interview had a significantly shorter duration compared to the routine sessions.…”
Section: Interview Conversation and Communication Strategiesmentioning
confidence: 99%
“…In a prospective randomised controlled observational study, Jadin et al . [ 16 ] reported that VAS for pre-operative anxiety was found 1.2 points lower (out of 10) after structured interview as compared to standard interview in younger patients (<47 years). Jlala et al .…”
Section: Discussionmentioning
confidence: 99%
“…Jadin et al . [ 16 ] reported no association of pre-operative anxiety with previous experience of anaesthesia, whereas, Jafar et al . [ 10 ] reported association of pre-operative anxiety with lack of previous surgical experience.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the mnemonic “InFARcT” ( In formation on diagnosis; F ollow-up; A dvice on self-care; R ed flags; c omplete T reatment) was shown to significantly improve recall [ 18 20 ]. Structuring the content of information given can take many forms; in pre-medication visits [ 22 ] the topics to be dealt with differ from discharge communication from patient to patient. So far however, improved recall of discharge information by explicitly structuring discharge information has only been shown in proxy patients (i.e.…”
Section: Introductionmentioning
confidence: 99%